Fiscal policy conditions for government budget stability and economic recovery: Comparative analysis of Japan and Greece - Naoyuki Yoshino; Farhad Taghizadeh-Hesary; Tetsuro Mizoguchi (Asian Development Bank Institute (ADBI), 2018)
In the literature regarding fiscal sustainability, the Domar condition and Bohn's condition are often used to check whether a government's debt situation is in a dangerous zone. This paper first shows that the Domar condition is obtained only from the government budget constraint (namely the supply of government bonds) and does not take into account the demand for government bonds. Second, this paper reveals that Bohn's condition does not satisfy the condition of economic stability: even if this is satisfied, economic recovery may not be achieved. This paper will propose a new condition that satisfies both the stability of the government budget and the recovery of the economy. The paper's empirical findings from Japan demonstrate that in order to achieve fiscal sustainability, both sides of the Japanese government budget (expenditure and revenue) must be simultaneously adjusted while the decline in government expenditure has to exceed the increase in tax revenue. In addition, the paper provides a comparative analysis of Japan and Greece as evidence of the aforementioned condition, and proves that although Japan's debt-to-GDP ratio is higher than that of Greece, its bond market remains stable. This is because it comes from the demand side of the market and investors have greater confidence in this economy due to its lower credit risk rooted in the country's macroeconomic strength and more auspicious economic future.
Keywords: E42; E63; 330; Japanese bond market; Greece economy; fiscal sustainability; fiscal policy condition; government debt management